Outfit between Needs and Requirements of Times: Maqashidi Analysis of al-A'raf [7]:31 - Assaidi, Sadullah (TSAQAFAH, 2024)
The question of hedonism has become commonplace because the tendency to smell earthly pleasure, luxury, or what is identical to wasting money for interests that are not for primary needs is a form of foya-foya and has taken root in a long-lasting habit, more related to style outfits. The discussion about outfits has been in the Qur'an, one of which is in QS. Al-A'raf [7]:31, which refers to the word az-zinatu. The interpreters of the Qur’an have interpreted it in various ways, such as treasures, jewelry, and clothing. The majority of the interpreters mean something that covers the body. As for the word israf in this verse, it is a way of excessive prohibition that leads to wastefulness and being trapped in hedonism. By using the Tafsir Maqashidi method, this article builds on previous interpretations of the terms az-zinatu and al-israf in particular, revealing that the behavior of israf is not only aimed at the health aspects of the body in the context of eating and drinking alone but also as an excessive ban on dressing. This article will show an understanding that excessive outfits can have a negative impact, up to mubazir. The use of the maqashidi tafsir method in this article is not only because this method is the latest, but it can also be used to understand various sentences such as social verses, science, and others. The result of this article is about the outfit in QS. Al-A’raf [7]: 31 indicates that the word israf also refers to the outfit of human beings. In addition, this article also focuses on the social aspect of QS. Al-A’raf [7]: 31 covers social relations to all mankind on earth in dress. Thus, this verse confirms that humans are wise in deciding behavior in outfits, as the words az-zinatu and al-israf become the basis for determining attitudes in order to achieve hifdz daulah and hifdz nafs, so that the maqashidi in this verse can be widely felt in the lives of human audiences in this world.